Glutathione S-Transferase Polymorphisms and Clinical Characteristics in Autism Spectrum Disorders - Mandic-Maravic, Vanja; Mitkovic-Voncina, Marija; Pljesa-Ercegovac, Marija; Savic-Radojevic, Ana; Djordjevic, Miroslav; Ercegovac, Marko; Pekmezovic, Tatjana; Simic, Tatjana; Pejovic-Milovancevic, Milica (Frontiers in Psychiatry, 2021)
Background: Autism spectrum disorders (ASD) are a heterogeneous group of developmental disorders, with different levels of symptoms, functioning and comorbidities. Recent findings suggested that oxidative stress and genetic variability in glutathione S-transferases (GSTs) might increase the risk of ASD development. We aimed to determine whether GST polymorphisms influence the severity of symptoms, as well as, cognitive and adaptive abilities in children with ASD. Methods: The sample included 113 ASD cases. All participants were genotyped for GSTA1, GSTM1, GSTT1 and GSTP1 polymorphisms. The clinical characteristics were determined with Autism Diagnostic Interview – Revised (ADI-R) in all of the participants. In non-verbal participants, we explored the adaptive functioning using Vineland Adaptive Behavior Scale II, while in verbal participants we used The Wechsler Abbreviated Scale of Intelligence (WASI). Results: It was shown that the GSTA1*CC genotype was a predictor of lower non-verbal communication impairment, as well as, a predictor of a lower chance of having seizures during life. GSTM1-active genotype predicted higher adaptive functioning. The predictive effect of GSTA1, GSTM1 and GSTT1 genotype was moderated by exposure during pregnancy (maternal smoking and medication). The GSTP1*IleIle genotype was significantly associated to better cognitive functioning in children with ASD. Conclusion: Besides the complex gene-environment interaction for the specific risk of developing ASD, there is also a possible complexity of interactions between genetic and environmental factors influencing the level of symptoms and impairment in people with ASD. Detoxification and antioxidant enzymes, such as GSTA1, might contribute to the core of this complexity.